2004
DOI: 10.1021/ja039587i
|View full text |Cite
|
Sign up to set email alerts
|

Probing Slow Dynamics in High Molecular Weight Proteins by Methyl-TROSY NMR Spectroscopy:  Application to a 723-Residue Enzyme

Abstract: A new CPMG-based multiple quantum relaxation dispersion experiment is presented for measuring millisecond dynamic processes at side-chain methyl positions in high molecular weight proteins. The experiment benefits from a methyl-TROSY effect in which cancellation of intramethyl dipole fields occurs, leading to methyl (13)C-(1)H correlation spectra of high sensitivity and resolution (Tugarinov, V.; Hwang, P. M.; Ollerenshaw, J. E.; Kay, L. E. J. Am. Chem. Soc. 2003, 125, 10420-10428). The utility of the methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
306
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(307 citation statements)
references
References 35 publications
0
306
0
1
Order By: Relevance
“…No evidence for dynamics was indicated when R ex ≈ 0 s −1 . For individual ILV methyl groups, the dispersion curves at 600, 800, and 900 MHz were fit to a two-state exchange model (A ⇌ B), yielding exchange rate constants (k ex = k AB + k BA ) (17,18). Under optimal conditions, the populations (p A and p B ) and the 13 C chemical shift differences between the two states, jΔω 13 Cj (in Hz, or jΔδ CPMG 13 Cj in ppm), were obtained for individual methyl groups (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence for dynamics was indicated when R ex ≈ 0 s −1 . For individual ILV methyl groups, the dispersion curves at 600, 800, and 900 MHz were fit to a two-state exchange model (A ⇌ B), yielding exchange rate constants (k ex = k AB + k BA ) (17,18). Under optimal conditions, the populations (p A and p B ) and the 13 C chemical shift differences between the two states, jΔω 13 Cj (in Hz, or jΔδ CPMG 13 Cj in ppm), were obtained for individual methyl groups (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…This is typically plotted as a relaxation dispersion curve, which can be fit to a two-state conformational exchange process (e.g., A ⇌ B interconversion). Fitting extracts the populations and the exchange rates between states, thus reflecting the thermodynamics and kinetics of the system (17,18).…”
mentioning
confidence: 99%
“…To better understand the slow motions (micro-to-millisecond timescale) on PmrA in the presence of DNA, we performed a series of NMR relaxation dispersion experiments, which are capable of probing invisible, low-populated conformations in protein folding, ligand binding and allosteric regulation [24][25][26] . Because of limited solubility and high molecular weight of the PmrA-DNA complex, we used methyl-TROSY relaxation dispersion experiments 27 to probe the slow dynamics in this complex. Methyl groups experiencing slow timescale motions show changes in effective relaxation rate, R 2,eff , measured as a function of the frequency of refocusing pulses n CPMG ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11). Measurements at both 600 and 850 MHz were fitted individually by use of the software relax 28 to a two-site exchange process (A2B), yielding populations (p A and p B ), exchange rate constants (k ex ¼ k AB þ k BA ) and the 1 H and 13 C chemical shift differences between the two states 27 (Supplementary Table 4). In total, 12 PmrA methyl groups exhibit slow dynamics on binding to DNA.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a series of relaxation dispersion experiments (Bouvignies et al 2010;Hansen et al 2008a, b;Korzhnev et al 2004;Loria et al 1999) suited for detecting conformational states that are poorly populated and thus only transiently visited. The results indicated that two variants-CAP-T127L/ S128I and CAP-S62F-cAMP 2 -underwent an exchange between conformational states on the microsecond-tomillisecond timescale Kalodimos 2009, 2012) (Fig.…”
Section: Allosteric Regulation By Slow Dynamicsmentioning
confidence: 99%